Functional Products Based on Goat Milk with the Addition of Natural Antioxidants: Scientific Review - Ansori, Firsty Ainun Zalzabila; Nisa, Fithri Choirun; Mubarok, Ahmad Zaki (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
The high consumer interest in functional food products not only provides basic nutrition but also adds health benefits. One of the nutrient-rich products is milk. Milk is an important and nutrient-high livestock product. Besides that, milk is also widely consumed by the people of Indonesia, one of which is goat milk. Goat milk has advantages such as having protein like breast milk, having high digestibility, and being able to be consumed by individuals who are allergic to cow's milk. Goat milk derivative products are quite diverse, including powdered goat milk, goat milk yogurt, and goat milk kefir. With its rich nutrition, goat milk has excellent potential to be developed as a functional product, especially by adding natural antioxidants. One of the ingredients in milk that can bind to antioxidants such as phenolic compounds is protein. As long as there is processing, both drying for milk powder products and the fermentation process for yogurt and kefir products can increase the antioxidant content of the final product which shows a synergistic effect on increasing the antioxidant content of the added natural ingredients. Milk protein can effectively bind to antioxidant compounds and strengthen the interaction between antioxidant compounds and casein so that the antioxidant content in the final product can be maintained. During the fermentation process, there is an increase in antioxidant value due to the activity of microbial enzymes produced during fermentation in binding and stabilization, where proteins such as casein and whey interact with antioxidant molecules like polyphenols and vitamins, forming more stable complexes. Efforts to increase the functional value of dairy products can increase antioxidant activity to ward off free radicals. Therefore, it is essential to review and analyze the various studies that have been conducted regarding the addition of natural antioxidants in goat milk to provide a comprehensive picture of the potential and challenges in the development of this product.